Pengaruh Pembangunan Daerah Melalui Community Development (Comdev) UPPKS Terhadap Kemiskinan Di Kecamatan Ngoro Kabupaten Jombang (Universitas Darul Ulum, 2020)
Community Development (comdev/community development) is an effort to develop a community condition in a sustainable and active manner based on the principles of social justice and mutual respect. Community workers seek to facilitate citizens in the process of creating social justice and mutual respect through broad development programs that connect all components of society. Community development translates the values ​​of openness, equality, responsibility, opportunity, choice, participation, mutual benefit, and continuous learning. The essence of community development is educating, enabling community members to do something by providing the necessary strength or advice and empowering them. The objectives to be achieved in this study are: to determine the effect of regional development on poverty alleviation efforts through the UPPKS Comdev program in Ngoro District, Jombang Regency. The approach in this research is descriptive quantitative, with multiple regression analysis. With the results of the study: That there is a significant influence on regional development on poverty alleviation efforts in Ngoro District, Jombang Regency. That there is no significant effect of Comdev UPPKS on poverty alleviation in Ngoro District, Jombang Regency. The lack of influence of the UPPKS Comdev program in Ngoro District, Jombang Regency is caused by aspects of increasing insight and knowledge; aspects of implementing leadership styles as well as aspects of providing capital assistance and the lack of ATTG (Appropriate Technology Tools) assistance received.